2020
DOI: 10.3390/cells9040918
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelet Lysate Can Replace Fetal Calf Serum as a Protein Source to Promote Expansion and Osteogenic Differentiation of Human Bone-Marrow-Derived Mesenchymal Stromal Cells

Abstract: Fetal calf serum (FCS) is frequently used as a growth factor and protein source in bone-marrow-derived mesenchymal stromal cell (BMSC) culture media, although it is a xenogenic product presenting multiple disadvantages including but not limited to ethical concerns. A promising alternative for FCS is human platelet lysate (hPL), which is produced out of human platelet concentrates and happens to be a stable and reliable protein source. In this study, we investigated the influence of hPL in an expansion medium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
(182 reference statements)
1
18
0
Order By: Relevance
“…Conversely, the expression of ALP and OPN decreased after 14 days of PPI treatment. The osteogenic marker genes are dynamically expressed during osteogenesis and often altered through protein supplementations [ 47 , 48 ]. Our results indicated that PPI was a potential modulator of the osteogenic gene expression, as compared to the well-established expression profile of osteogenic gene markers [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the expression of ALP and OPN decreased after 14 days of PPI treatment. The osteogenic marker genes are dynamically expressed during osteogenesis and often altered through protein supplementations [ 47 , 48 ]. Our results indicated that PPI was a potential modulator of the osteogenic gene expression, as compared to the well-established expression profile of osteogenic gene markers [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported an increase in the differentiation potential of several types of MSCs towards the osteogenic, myofibroblastic, cardiomyogenic and adipogenic cell lineages in the presence of pHPL as a serum substitute ( Karadjian et al, 2020 ; Samuel et al, 2016 ; Chignon-Sicard et al, 2017 ; Homayouni Moghadam, Tayebi & Barzegar, 2016 ). On the other hand, pHPL decreased the ability of certain types of stem cells to differentiate into osteoblasts, chondrocytes and adipocytes ( Gruber et al, 2004 ; Lee et al, 2014 ; Chignon-Sicard et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs and hES-MP cells were grown in DMEM/F12+ Glutamax medium (Gibco, Grand Island, NY, USA), 1% penicillin/streptomycin (Gibco), and either 10% hPL (hPL–hES-MP and hPL–MSC treatments/cells) or 10% FBS (FBS–hES-MP and FBS–MSC treatments/cells). The decision to use 10% hPL was made after evaluating different hPL concentrations; our group typically uses 10% hPL in studies with bone marrow-derived MSCs, and this concentration has been investigated in other studies [ 30 , 31 , 32 ], which matches the typical concentration of FBS used for supplementation.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were maintained at standard culture conditions, and the cell count was determined at the end of each passage using a Neubauer hemocytometer (Assistant, Munich, Germany). The number of PDs at each passage was then used to find the cumulative PDs (CPDs) using Equations (1) and (2), as previously described [ 28 , 32 ]: where N 0 and N H represent the number of cells seeded and the number of cells harvested (at the end of the expansion period), respectively, and n represents the number of passages.…”
Section: Methodsmentioning
confidence: 99%